2004
DOI: 10.1007/s00401-004-0882-7
|View full text |Cite
|
Sign up to set email alerts
|

?-Internexin aggregates are abundant in neuronal intermediate filament inclusion disease (NIFID) but rare in other neurodegenerative diseases

Abstract: Abnormal neuronal aggregates of α-internexin and the three neurofilament (NF) subunits, NF-L, NF-M, and NF-H have recently been identified as the pathological hallmarks of neuronal intermediate filament (IF) inclusion disease (NIFID), a novel neurological disease of early onset with a variable clinical phenotype including frontotemporal dementia, pyramidal and extrapyramidal signs. α-Internexin, a class IV IF protein, a major component of inclusions in NIFID, has not previously been identified as a component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 32 publications
3
57
1
Order By: Relevance
“…Generally, the NIIs were more intensely labelled by anti-ubiquitin antibodies than were the cytoplasmic inclusions. Previously, we have shown that some, generally compact, NCIs are only weakly or unstained by ubiquitin IHC [1,6]. With ubiquitin IHC, the NIIs appeared round, sometimes elongated, occasionally occupying more than 50% of the nuclear volume.…”
Section: Niis Of Nifid Are Intensely Ubiquitinatedmentioning
confidence: 74%
See 2 more Smart Citations
“…Generally, the NIIs were more intensely labelled by anti-ubiquitin antibodies than were the cytoplasmic inclusions. Previously, we have shown that some, generally compact, NCIs are only weakly or unstained by ubiquitin IHC [1,6]. With ubiquitin IHC, the NIIs appeared round, sometimes elongated, occasionally occupying more than 50% of the nuclear volume.…”
Section: Niis Of Nifid Are Intensely Ubiquitinatedmentioning
confidence: 74%
“…Antibodies used included those that recognise ubiquitin, expanded polyglutamine repeats, and epitopes of class IV neuronal IF proteins including phosphorylation-dependent and non-phosphorylation-dependent anti-neuronal IF antibodies ( Table 2). Anti-neuronal IF antibodies used in this study are well characterised and have been used previously to demonstrate epitopes of neuronal IFs in NIFID [4,6,7].…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…This disease was first described in 2004 in a series of reports by Cairns et al (62,63). Microscopically, this disease is characterized by neuronal IF inclusions that contain neither synuclein nor tau.…”
Section: Neuronal If Inclusion Disease a Recently Described Disease mentioning
confidence: 99%
“…α-Internexin has recently been identified as a major component of the pathological inclusions of the frontotemporal dementia, neuronal intermediate filament inclusion disease (NIFID) (Figure 2). The signature lesion of this disease is the neuronal cytoplasmic inclusion, which is tau-and α-synuclein negative, variably ubiquitinated, and contains epitopes of all type IV IF proteins [59][60][61]. In addition to NFs in swollen axons and spheroids in ALS, peripherin has also been demonstrated by immunohistochemistry (IHC) in the ubiquitinated inclusions of ALS [62].…”
Section: Neuronal Ifs and Diseasementioning
confidence: 99%